Assessing Reserve Adequacy : Further Considerations. (Policy Papers; Policy Paper ;, 2013)
Reserves remain a critical liquidity buffer for most countries. They are generally associated with lower crisis risks (crisis prevention) as well as space for authorities to respond to shocks (crisis mitigation). While other instruments, such as official credit lines and bilateral swap lines, are also external buffers, for most countries they principally act as a complement to their official reserves. For countries with sound fundamentals and a good policy framework, reserves provide policy makers with considerable space to respond to transitory shocks. However, this space diminishes as fundamentals deteriorate and the existence of adequate reserves does not, by itself, eliminate the risk of market pressures.